2022
DOI: 10.1101/2022.04.12.22273780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Malaria and typhoid fever coinfection among patients presenting with febrile illnesses in Ga West Municipality, Ghana

Abstract: Background: Malaria and typhoid fever coinfection presents major public health problems especially in the tropics and sub-tropics where malaria and typhoid fever are co-endemic. Clinicians often treat both infections concurrently without laboratory confirmation. However, concurrent treatment has public health implications as irrational use of antibiotics or anti-malarials may lead to the emergence of drug resistance, unnecessary cost and exposure of patients to unnecessary side effects. This study determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…e prevalence of culture-confirmed typhoid fever was 6.5% CI: (4.3-9.1)]. is finding is more or less similar to previous studies done in Shashemene, Ethiopia (5.0%) [22], West, Ghana (6.37%) [31], Northern, Uganda (6.8%) [20], and Kolkata, India (4.5%) [27]. e prevalence is much lower than the extent of prevalence stated in Northern Ethiopia (68.7%) (17), Nigeria (12%-40%) [32], Northern India (22%) [33], and Karnataka, India (55.4%) [34].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…e prevalence of culture-confirmed typhoid fever was 6.5% CI: (4.3-9.1)]. is finding is more or less similar to previous studies done in Shashemene, Ethiopia (5.0%) [22], West, Ghana (6.37%) [31], Northern, Uganda (6.8%) [20], and Kolkata, India (4.5%) [27]. e prevalence is much lower than the extent of prevalence stated in Northern Ethiopia (68.7%) (17), Nigeria (12%-40%) [32], Northern India (22%) [33], and Karnataka, India (55.4%) [34].…”
Section: Discussionsupporting
confidence: 86%
“…This finding agrees with the results reported for Ghana (1.91%) [ 38 ], India (1.6% and 1.59%) [ 33 , 36 ], and Pakistan (4%) [ 30 ]. In contrast, the current coinfection prevalence is lower than reported in KMC&H, Guntur (6.5%) [ 39 ], Cameroon (7.8%) [ 15 ], Enugu, Nigeria (15.6%) [ 31 ], Calabar, Nigeria (28%) [ 21 ], Southeastern Nigeria (36.2%) [ 28 ], and Akure, Nigeria (51.5%) [ 40 ]. The low prevalence of malaria-typhoid fever coinfection in our study might be due to the test methods employed for the diagnosis of malaria and typhoid fever.…”
Section: Discussionmentioning
confidence: 94%
“…The reason that could be ascribed to this observation was probably due to the differences in the prevalence of malaria in these study sites. The prevalence of malaria in the Ga West Municipality, a contiguous district to the study site for the Aninagyei (2020) study, was reported to be 36.3% [ 33 ], which was significantly higher than the prevalence of malaria in Kwahu-South (11.9%) [ 34 ], a contiguous district to the New Juaben South Municipality, the study district for this study. Secondly, the study site for the previous study was peri-urban while that of this study was urban.…”
Section: Discussionmentioning
confidence: 99%
“…Typhoid fever and malaria share many similar signs and symptoms. As a result, the feverish patient may receive incorrect diagnosis and treatment due to the similar clinical features of the two illnesses (Birhanie et al, 2014;Tanko Rufai et al, 2022). The intertwined challenges of malaria and typhoid fever underscore the importance of accurate diagnosis and appropriate management to mitigate the burden of these diseases in endemic regions.…”
Section: Malaria and Typhoid Co-infection -Typhomalariamentioning
confidence: 99%